Dendrimer‐Type Peptoid‐Decorated Hexaphenylxylenes and Tetraphenylmethanes: Synthesis and Structure in Solution and in the Gas Phase. Issue 49 (8th October 2014) - Peschko, Katharina; Schade, Alexandra; Vollrath, Sidonie B. L.; Schwarz, Ulrike; Luy, Burkhard; Muhle‐Goll, Claudia; Weis, Patrick; Bräse, Stefan
Abstract Branched organic nanostructures are useful scaffolds that find multiple applications in a variety of fields. Here, we present a novel approach to dendrimer‐like structures. Our design contains a rigid hydrocarbon‐based core (hexaphenylxylylene/tetraethynylphenylmethane) combined with a library of N‐substituted oligoglycines (so‐called peptoids) providing a flexible shell. The use of click chemistry allows rapid assembly of the nanostructures. The possibility of tuning the size and the solubility of this new type of nanostructure will be advantageous for future applications such as heterogeneous catalysis.